Appellations of geographical origin as a generator of national competitiveness - Jovićević-Simin Marina; Jovićević Predrag; Novaković Srđan (Ekonomika Poljoprivrede (1979), 2016)
The protection of appellations of geographical origin worldwide, through the Lisbon Agreement mainly refers to agricultural and food products and the leading countries in the number of registrations of appellations of origin are: France, Czech Republic, Bulgaria, Italy etc. By the product structure 85% of registrations of appellations of origin in the world refer to the four major categories of food products such as: wine (61.5%), spirits (9.5%), agricultural products (8.4%) and cheese (8.5%). Considering that the protection of appellations of geographical origin in Serbia is mainly related to agricultural and food products, and the fact that we have 52 domestic and only 3 internationally protected appellations of origin, these could be used as a powerful tool to support the growth of competitiveness in agriculture of certain regions as well as of the entire country. Appellations of geographical origin have a collective ownership and represent a kind of national resource.